The Role of Strategic Management in Achieving Sustainable Development Goals - Al-Malkie, Ibtesam Ahmed; Al-Tally, Hasan Ahmed (Journal of Economic, Administrative and Legal Sciences, 2025)
This study aimed to explore the role of strategic management in achieving sustainable development goals within government departments in the city of Abha. The research problem stems from the urgent need to understand how the dimensions of strategic management (environmental analysis, strategy formulation, strategy implementation, monitoring and evaluation) contribute to supporting sustainable development across its dimensions (economic, social, environmental, and technological), especially in light of the increasing contemporary challenges facing public administration. The importance of the study lies in highlighting the relationship between strategic management and the achievement of sustainable development as a strategic choice that enhances institutional governmental performance. The study was based on the main hypothesis that there is a statistically significant relationship between the dimensions of strategic management and the achievement of sustainable development goals. The researcher adopted a descriptive-analytical approach, with a research sample consisting of 356 individuals, including employees and department managers, selected using a random sampling method. The questionnaire was distributed electronically to the study sample. The study found that government departments recognize the importance of strategic management, including environmental analysis, strategy formulation, implementation, and monitoring and evaluation. Among the sustainable development goals in government departments, economic aspects ranked first in importance, followed by technological, environmental, and social dimensions. The findings also indicated a statistically significant relationship between the dimensions of strategic management (environmental analysis, strategy formulation, strategy implementation, monitoring, and evaluation) and the dimensions of sustainable development (economic, social, environmental, and technological) within government departments in Abha. The study recommended the establishment of an effective and continuous strategic information system to collect and analyze data on the external environment surrounding government entities. This would help identify factors that positively affect the efficiency of government performance and capitalize on them, as well as recognize negative factors and work to mitigate their impact.